Answer:
C. In y^2-y=6, 6 should have been subtracted on both sides first.
Step-by-step explanation:
It is a quadratic equation so you subtract the 6 and create
y^2-y-6=0
Then you factor it to:
(y-3)(y+2)=0
The solutions then are:
y-3=0, y=3 and y+2=0, y=-2
{-2,3}
This is a geometric sequence since there is a common ratio between each term. In this case, multiplying the previous term in the sequence by <span>33</span> gives the next term. In other words, <span><span><span>an</span>=<span>a1</span>⋅<span>r<span>n−1</span></span></span><span><span>an</span>=<span>a1</span>⋅<span>r<span>n-1</span></span></span></span><span>.</span>
6·4=24
if they want you to find out how many peaches all of them picked together, its 24·3